The TRADITIONAL CHINESE MEDICINE FOR CENTRAL SEROUS CHORIORETINOPATHY: A CASE SERIES WITH OPTIC COHERENCE TOMOGRAPHY SCANS - SU, Chun-Feng; LIN, Ching-Huang; FAN, Qiao (African Journal of Traditional, Complementary and Alternative Medicines, 2024)
Background: The aim of this study was to investigate a potential therapy for central serous chorioretinopathy (CSC) using Traditional Chinese Medicine (TCM). Materials and Methods: Six males aged 28-45 with CSC were treated with a TCM formula called Bupleurum and Poria Variant Decoction (Jia Jian Chai Ling Tang), in the form of concentrated powder herbs (4.0 g) taken before meals, three times daily. They were monitored clinically with optic coherence tomography (OCT) scans every one or two weeks until CSC symptoms completely resolved. Results: All six cases showed clinical improvement after receiving the prescribed treatment, with subretinal serous fluid progressively decreasing within 3 weeks to 3 months based on follow-up OCT scans. Conclusions: The patients with CSC responded positively to the Jia Jian Chai Ling Tang prescription, indicating a potential new approach for treating CSC. This study suggests a promising avenue for further exploration in CSC treatment options.